MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN EFEKTIVITAS PEMBELAJARAN DI SEKOLAH DASAR: STUDI KASUS SDN 1 METRO SELATAN - Dwi Saputro; Maiko Sabri Martha; Apri Wahyudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of Human Resource Management (HRM) and its impact on learning effectiveness at SDN 1 Metro Selatan. Using a qualitative approach with an intrinsic case study, this study aims to describe the implementation of HRM, analyze the level of learning effectiveness, and identify the influence of HRM on improving learning effectiveness. Data were collected through in-depth interviews, observations, and documentation studies with the principal, teachers, and administrative staff. The results indicate that the implementation of HRM at SDN 1 Metro Selatan is running well, focusing on continuous teacher competency development, nurturing supervision, and transformational leadership that creates a collaborative work climate. Learning effectiveness is high, characterized by good student learning outcomes, active student activities, and teachers' ability to manage innovative learning. It was found that the implementation of HRM, particularly in the development and leadership functions, has a significant influence on improving learning effectiveness. Competent and motivated teachers, as a result of good HRM, are a direct determinant of the quality of classroom learning.